(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The objective of this project, employing the HRSD, is to advance the comprehension, prevention, and management of depression among industrial workers, thereby promoting their mental health and well-being. The project seeks to pinpoint specific risk factors within industrial workplaces that contribute to depression among employees. Through HRSD assessments, alongside surveys or interviews, researchers intend to investigate factors such as job demands, organizational culture, interpersonal relationships at work, and exposure to hazardous working conditions. The project also aims to assess the prevalence of occupational burnout among employees in a pharmaceutical company and its correlation with depressive symptoms.